E-commerce engineering: A short vs long software process for the development of e-commerce applications - Pitsillides, Andreas; Mavromoustakos, Stephanos; Schizas, Christos N.; Andreou, Andreas S.; Samaras, George; Chrysostomou, Chrysostomos; Leonidou, Costas (My University, 2003)
The immediacy in developing e-commerce applications, the quality of the services offered by these systems band the need for continuous evolution are primary issues that must be fully analysed and understood prior and during the development process. In this context, the present work suggests a new development framework which aims at estimating the level of complexity a certain e-commerce system encompasses and driving the selection of a long or short software process in terms of time and effort. The proposed framework utilizes a special form of Business Process Re-engineering (BPR) to define and assess critical business and organizational factors within small-to-medium enterprises (SMEs) whishing to go ecommerce. This set of factors is enriched with other critical issues belonging to the quality requirements of the system and to the application type of services it aspires to offer. The set of critical factors identified is used to estimate the average complexity level of the system using numerical values to describe the contribution of each factor to the overall complexity. The level of complexity estimated dictates the adoption of either a short or a long version of the well-known WebE process for analysing, designing and implementing the e-commerce system required by an SME.
Keywords: BPR | Complexity | E-commerce | SME | Software process